2007
DOI: 10.1074/jbc.m610775200
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation, Quantitative Refinement, and in Vivo Utilization of the HOXA13 DNA Binding Site

Abstract: Mutations in Hoxa13 cause malformations of the appendicular skeleton and genitourinary tract, including digit loss, syndactyly, and hypospadias. To determine the molecular basis for these defects, the DNA sequences bound by HOXA13 were empirically determined, revealing a novel high affinity binding site. Correlating the utilization of this high affinity binding site with genes exhibiting perturbed expression in Hoxa13 mutant limbs, we identified that HOXA13 suppresses the expression of the BMP antagonist, Sost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…5I). Genes associated with joint interzone development or function, including Wnt9a (Archer et al, 2003;Pacifici et al, 2006) and doublecortin (Zhang et al, 2011;Zhang et al, 2007), as well as the BMP inhibitor sclerostin domain-containing protein 1 (Sostdc1) (Guo et al, 2010;Knosp et al, 2007), were also found to be expressed at significantly higher levels in Gdf5-treated cells than in the BMP4-treated populations (Fig. 5J-L).…”
Section: Research Articlementioning
confidence: 98%
“…5I). Genes associated with joint interzone development or function, including Wnt9a (Archer et al, 2003;Pacifici et al, 2006) and doublecortin (Zhang et al, 2011;Zhang et al, 2007), as well as the BMP inhibitor sclerostin domain-containing protein 1 (Sostdc1) (Guo et al, 2010;Knosp et al, 2007), were also found to be expressed at significantly higher levels in Gdf5-treated cells than in the BMP4-treated populations (Fig. 5J-L).…”
Section: Research Articlementioning
confidence: 98%
“…The gene has also been called Sostdc1 (Sclerostin domain-containing 1) or Sostl (Sclerostin-like) due to the homology with Sclerostin-encoding gene Sost (4,5). USAG-1/Wise/Ectodin/Sostdc1 is expressed in various tissues, such as the surface ectoderm of the posterior axis (1,6), branchial arches (3,6), the dermal papilla in hair follicles (7), vibrissae (3), mammalian tooth cusps (3,8), rat endometrium (2), developing testis (9 -11), interdigital tissues (12), and embryonic and adult kidneys (13,14).…”
mentioning
confidence: 99%
“…HOXA13 is a transcriptional factor that negatively regulates USAG-1 expression. 27 We observed that renal expression of HOXA13 was significantly increased in the Ad þ SIM group compared with the Ad group (Figure 3h). These data indicate that SIM not only suppressed fibrotic pathway, but also enhanced anti-fibrotic pathway by downregulating a dominant BMP-7 antagonist USAG-1, and not by enhancing BMP-7 production.…”
Section: Evaluation Of the Molecules Associated With Fibrosis And Antmentioning
confidence: 81%
“…On the basis of the previous observation that homeobox protein Hox-A13 (HOXA13), a transcriptional factor, binds to USAG-1 coding DNA region and regulates USAG-1 expression in organogenesis, 27 0 . Subsequently, the cells were kept in serum-free medium for 24 h, and then they were placed into the 1% FBS-added medium containing recombinant human 5 ng/ml TGF-b1 (Sigma-Aldrich, St Louis, MO, USA) with or without 0.2 mM SIM for 72 h. 28,29 We decided the concentration of SIM to reduce toxicity and preserve efficacy of SIM based on the result of our preliminary experiments showing that MDCK cells were detached by 2 mM SIM treatment and USAG-1 expression was not changed by 0.02 mM SIM treatment (data not shown).…”
Section: Pathological Analysismentioning
confidence: 99%
See 1 more Smart Citation